Instability due to unrecognised fracture-subluxations after apparently isolated injuries of the cervical spine. - Madhavan, P; Monk, J; Wilson-MacDonald, J; Fairbank, J (2001)
Instability may present at a different level after successful stabilisation of an unstable segment in apparently isolated injuries of the cervical spine. It can give rise to progressive deformity or symptoms which require further treatment. We performed one or more operations for unstable cervical spinal injuries on 121 patients over a period of 90 months. Of these, five were identified as having instability due to an initially unrecognised fracture-subluxation at a different level. We present the details of these five patients and discuss the problems associated with their diagnosis and treatment.